2022
DOI: 10.1021/acscatal.1c05947
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Intrinsic Active Sites for the Selective Catalytic Reduction of Nitric Oxide on Metal-Free Carbon Catalysts via Selective Passivation

Abstract: Although carbon catalysts have been commercialized for the low-temperature selective catalytic reduction (SCR) of NO with NH 3 for decades, the nature of the active sites remains unclear. Herein we design a proof-of-concept study to directly evidence that the nucleophilic ketonic carbonyl groups are the intrinsic SCR active sites on metal-free carbon catalysts through ex situ and in situ selective passivation strategies. The turnover frequency of the ketonic carbonyl group is provided, and the structure−reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 28 publications
2
18
0
Order By: Relevance
“…In this study, we found that the carbon catalysts with similar contents of ketonic carbonyl and phenol groups but different contents of carboxyl groups exhibited similar SCR activities under the same reaction conditions (Figures , , and ), indicating that the carboxyl groups may not contribute to the SCR activity. This result is in accordance with the outcome of our previous study, in which the electrophilic carboxyl groups were clarified to act as spectators in SCR reactions through selective passivation and quasi- in situ XPS . These results clearly indicated that carboxyl groups served as inactive sites in the SCR reaction.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…In this study, we found that the carbon catalysts with similar contents of ketonic carbonyl and phenol groups but different contents of carboxyl groups exhibited similar SCR activities under the same reaction conditions (Figures , , and ), indicating that the carboxyl groups may not contribute to the SCR activity. This result is in accordance with the outcome of our previous study, in which the electrophilic carboxyl groups were clarified to act as spectators in SCR reactions through selective passivation and quasi- in situ XPS . These results clearly indicated that carboxyl groups served as inactive sites in the SCR reaction.…”
Section: Resultssupporting
confidence: 92%
“…Currently, SCR technology along with carbon catalysts have been large-scale applied in steel sintering through a reaction–regeneration process which consists of a catalytic reactor and a regenerator (Figure ). It is well established that the surface of a carbon catalyst is dominated by plenty of oxygen-containing groups, and our recent study identified that the ketonic carbonyl group is the SCR active site . Under this sense, special attention should be paid to the SCR catalytic inactive sites.…”
Section: Environmental Implicationsmentioning
confidence: 95%
See 2 more Smart Citations
“…Finally, the NH 4 + detected in the catalytic system reacts with OH* to complete the overall pathway, accompanied with the generation of NH 3 and H 2 O. Therein, the first N–H bond breakage is the rate-determining step. For the E–R mechanism, the absorbed NH 3 * first dissociates the N–H bond with an energy barrier of 1.23 eV and then reacts with NO 2 to form NH 2 NO 2 *, which undergoes a multistep bond breakage to generate N 2 . Specifically, this process does not require N–N coupling in contrast to the L–H mechanism.…”
Section: Resultsmentioning
confidence: 99%